2016
DOI: 10.1111/pace.12913
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiography Screening for Hypertrophic Cardiomyopathy

Abstract: Computer-automated ECG screening for HCM is feasible. Evaluation of automated ECG algorithms in larger and more diverse populations is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These insights indicate that while ECG can provide valuable information, it may not be comprehensive enough for accurate HCM identification when used in isolation. [34][35][36] Despite advancements, at present the diagnosis of HCM still must involve a combination of tests including echocardiography, genetic testing, and clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…These insights indicate that while ECG can provide valuable information, it may not be comprehensive enough for accurate HCM identification when used in isolation. [34][35][36] Despite advancements, at present the diagnosis of HCM still must involve a combination of tests including echocardiography, genetic testing, and clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study concentrated on classifying HCM patients through ECG analysis. These insights indicate that while ECG can provide valuable information, it may not be comprehensive enough for accurate HCM identification when used in isolation (27)(28)(29). Despite advancements, at present the diagnosis of HCM still must involve a combination of tests including echocardiography, genetic testing, and clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Previous studies had indicated that a computer-automated ECG screening algorithm can perform well in cardiomyopathy screening. [16] Moreover, our model was constructed from statistical frameworks, therefore, although the procedure of interpretation of ECG was left out for reducing the requirement of medical expertise, our model was easier to explain than models constructed from machine learning without the "black box" phenomena. [17] Historically, many electro cardiologists and clinicians have continuously explored the relationship between ECG and cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%